Seasonal Prevalence and Insecticide Susceptibility Status of Phlebotomine Sandflies (Diptera : Psychodidae) in the North-Western Thar Desert (District Bikaner, Rajasthan) - Bansal, S K; Chaudhary, R C; Singh, Karan V; Lakshminarayana, J (Annals of Arid Zone, 2016)
Astudywas carried out on the seasonal prevalence and insecticide susceptibility status of phlebotomine sandflies in different villagesof district Bikaner during 1994-1995. Five species of sandflies viz. Phlebotomus paparasi (71.1%), Sergentomyia punjabel1sis (19.0%), S. babu babu (7.3%), S. c1ydei (1.8%) and S. baghdadis (0.8%) were collected from indoor habitats like human dwellings, cattle sheds and rodent burrows. Maximum density of all the sandflies was observed during the monsoon and post-monsoon season (July-October) followed by spring (March and April), summer (May and June) and winter season (November to February). P. papatasi revealed that it is susceptible to fenitrothion and permethrin, resistant to DDT, dieldrin and propoxur while a verification was required with malathion. LC50 values for DDT and dieldrin were 4.3 and 0.43%, respectively, while LT50 values for fenitrothion, propoxur and permethrin were 42.6, 50.0 and 15.7 minutes, respectively.